Human Resource Management Development At PT. Damar Outsourcing Anugrah - As, Zuherman; Suwarni, Suwarni; Soleh, Ahmad (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2026)
This research aims to analyze the development of human resource management (HRM) at PT. Damar Outsourcing Anugrah, a company that provides labor services in the fields of security and cleanliness, operating in Bengkulu Province. Human resource management is a key factor in determining the company's success, particularly in the outsourcing industry, which heavily relies on the quality, competence, and loyalty of the workforce.(1) This study employs a qualitative approach with a descriptive method, utilizing techniques such as observation, interviews, and documentation involving the management and employees of PT. Damar Outsourcing Anugrah. The primary focus of the research includes aspects of employee recruitment, placement, training, and career development. The research findings indicate that the company has implemented a systematic recruitment process in line with work competency standards, places workers based on their qualifications and client needs, and provides training to enhance employees' technical and non-technical skills. Additionally, the company has established a career development system to boost motivation and loyalty among the workforce.(2) In terms of the human resource development variable, the company has made efforts to apply the principles of Human Capital Management (HCM) by viewing human resources as a long-term investment asset. However, challenges persist, such as high turnover rates, a lack of sense of ownership toward the company, and limited career opportunities for outsourcing workers. Therefore, a more comprehensive human resource development strategy is required, including enhanced continuous training, structured career planning, and the implementation of a digital-based human resource management system to enable the company to compete sustainably.